Neuroprotective and plasticity promoting effects of repetitive transcranial magnetic stimulation (rTMS): A role for microglia - Paolo d’Errico; Iris Früholz; Melanie Meyer-Luehmann; Andreas Vlachos (Brain Stimulation)
Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive brain stimulation technique used to modulate neocortical excitability, with expanding applications in neurological and psychiatric disorders. However, the cellular and molecular mechanisms underlying its effects, particularly the role of microglia –the resident immune cells of the central nervous system– remain poorly understood. This review synthesizes recent findings on how different rTMS protocols influence microglial function under physiological conditions and in disease models. Emerging evidence indicates that rTMS modulates microglial activation, promoting neuroprotective and plasticity-enhancing processes not only in models of brain disorders, such as Alzheimer's and Parkinson's disease, but also in healthy neural circuits. While much of the current research has focused on the inflammatory profile of microglia, critical aspects such as activity-dependent synaptic remodeling, phagocytic activity, and process motility remain underexplored. Given the substantial heterogeneity of microglial responses across brain regions, age, and sex, as well as their differential roles in health and disease, a deeper understanding of their involvement in rTMS-induced plasticity is essential. Future studies should integrate selective microglial manipulation and advanced structural, functional, and molecular profiling techniques to clarify their causal involvement. Addressing these gaps will be pivotal in optimizing rTMS protocols and maximizing its therapeutic potential across a spectrum of neurological and neuropsychiatric conditions.